2016
DOI: 10.1186/s12889-016-3478-y
|View full text |Cite
|
Sign up to set email alerts
|

Health or harm? A cohort study of the importance of job quality in extended workforce participation by older adults

Abstract: BackgroundAs people are living longer, they are being encouraged to work longer. While it is assumed that extended employment will be good for health, the evidence has been mixed. This study considers whether employment and job quality exert an influence on four indicators of health status in older workers.MethodsData for this study came from 836 older workers (440 men and 396 women) aged 50–59 years at baseline who participated in the Household, Income and Labour Dynamics in Australia (HILDA) Survey. Using li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
(35 reference statements)
2
33
0
1
Order By: Relevance
“…This is the first longitudinal study to compare work with other community organizations by defining work as a type of social participation. Previous longitudinal studies focusing on the relationship between work and health outcomes among older people have examined work alone [20,36,37], and comparisons with other community organizations have been cross-sectional studies [38]. Given the current challenges posed by a rapidly declining birthrate and aging population, it is necessary to develop a social structure where many older people work [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first longitudinal study to compare work with other community organizations by defining work as a type of social participation. Previous longitudinal studies focusing on the relationship between work and health outcomes among older people have examined work alone [20,36,37], and comparisons with other community organizations have been cross-sectional studies [38]. Given the current challenges posed by a rapidly declining birthrate and aging population, it is necessary to develop a social structure where many older people work [39].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that working support and improvement of working environment could be public health policies that would prevent the need for the provision of long-term care in rural and urban areas. In longitudinal studies of work and health outcomes [20,36,37], work is generally considered good for health. However, poor-quality work [36] is not good for health; therefore, additional analysis is necessary, since this research did not consider the type of work.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Surgeon General conclusion in 2014, the greatest danger to public health is from cigarettes and other combustible products [ 14 , 15 ]. At the same time, smokeless tobacco and alternative nicotine delivery systems have improved and it is evidence-based that they are less harmful than cigarettes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing knowledge, all tobacco products—smokeless, smoked tobacco, and cigarette substitutes—are harmful and addictive and all can cause disease and death [ 11 ]. However, current scientific evidence also indicates that tobacco products differ in related health harm [ 12 , 13 , 14 ]. Combustible tobacco products (including all types of cigarettes without any exception) inhaled into the lungs are ranked as the most harmful, while non-combustible products are assessed to be relatively less harmful [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation